2003
DOI: 10.1002/eji.200324550
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 10 regulates cell surface and soluble LIR‐2 (CD85d) expression on dendritic cells resulting in T cell hyporesponsiveness in vitro

Abstract: Dendritic cells (DC) are unique in their ability to stimulate naive T cells to proliferate and to differentiate into effector T cells. DC, however, can also inhibit T cell activation and play a role in central and peripheral tolerance. IL-10 has been shown to render DC tolerogenic by unknown mechanisms. Using a combined monoclonal antibody/retroviral expression cloning approach, we show here that the inhibitory receptor LIR-2 (leukocyte immunoglobulinlike receptor-2, CD85d) is specifically up-regulated by IL-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
57
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 29 publications
4
57
0
1
Order By: Relevance
“…This effect was suggested to result from competition between membrane ILT4, which is inhibitory, and soluble ILT4 for binding to MHC class I molecules on T cells (17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This effect was suggested to result from competition between membrane ILT4, which is inhibitory, and soluble ILT4 for binding to MHC class I molecules on T cells (17).…”
Section: Discussionmentioning
confidence: 99%
“…ILT4 binds to HLA class I molecules (14,(17)(18)(19) and its murine homolog was shown to be the paired Ig-like receptor (PIR)-B (20,21). Using an experimental model of chronic antigenic stimulation of recipient rats with UVBirradiated blood from their donor, we demonstrated that CD8 ϩ FOXP3 ϩ Ts cells mediate tolerance to allogeneic heart transplants, inducing PIR-B in donor DC and EC and rendering the graft resistant to rejection (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A diferencia del sILT4, el sILT3 muestra una fuerte actividad inhibidora (92), lo cual confirma que ILT3 tiene efectos tanto intracelulares como extracelulares, mientras que ILT4 sólo ejerce efectos inhibidores a nivel intracelular, bloqueando la diferenciación de la célula presentadora de antígeno. El sILT3, además, inhibe la "alorreactividad" de las células T CD8+ en células T supresoras antígeno-específicas Foxp3+ y no induce inmunosupresión inespecífica debido a que actúa solamente sobre células T activadas (93).…”
Section: Proteasomaunclassified
“…Therefore, maintaining iDC in an immature steady state is critical for inducing long-term immune tolerance in vivo. Recent studies revealed a certain DC subset with potent immunoregulatory properties in humans and mice, which can be generated by culturing bone marrow-derived dendritic cells (BMDCs) in the presence of inhibitory cytokines such as interleukin (IL)-10 or transforming growth factor (TGF)- (4,5). This DC subset possesses characteristics of a low-expressing mature marker (CD83) and costimulatory molecules that can induce T-cell hyporesponsiveness, promote the generation of regulatory T cells (Tregs), and prolong allograft survival.…”
Section: Introductionmentioning
confidence: 99%